Resolving dynamic fragmentation of liquids at the nanoscale with ultrafast small‐angle X‐ray scattering. (1st August 2019) - Chen, Sen; Chai, Hai-Wei; He, An-Min; Tschentscher, Thomas; Cai, Yang; Luo, Sheng-Nian
Abstract : The feasibility is explored of resolving ultrafast fragmentation of liquids at the nanoscale with single‐shot small‐angle X‐ray scattering on the basis of large‐scale molecular dynamics simulations. From the simulated SAXS patterns, particle‐volume size distributions are obtained with the regularization method and average particle sizes with the weighted Guinier method, at different expansion rates. Abstract : High‐brightness coherent ultrashort X‐ray free‐electron lasers (XFELs) are promising in resolving nanoscale structures at the highest temporal resolution (∼10 fs). The feasibility is explored of resolving ultrafast fragmentation of liquids at the nanoscale with single‐shot small‐angle X‐ray scattering (SAXS) on the basis of large‐scale molecular dynamics simulations. Fragmentation of liquid sheets under adiabatic expansion is investigated. From the simulated SAXS patterns, particle‐volume size distributions are obtained with the regularization method and average particle sizes with the weighted Guinier method, at different expansion rates. The particle sizes obtained from simulated SAXS are in excellent agreement with direct cluster analysis. Pulse‐width effects on SAXS measurements are examined. The results demonstrate the feasibility of resolving the nanoscale dynamics of fragmentation and similar processes with SAXS, and provide guidance for future XFEL experiments and data interpretation.